655 The Role of Insomnia Symptoms in the Relation between Perceived Vulnerability to Disease and COVID-19 Anxiety. (3rd May 2021) - Campbell, Rebecca; Walker, Jamie; Makhanova, Anastasia; Vargas, Ivan
Abstract: Introduction: Individuals who report greater perceived vulnerability to disease (e.g., experience emotional discomfort to situations where pathogen transmission is likely) also have the tendency to endorse more anxiety. Insomnia is also associated with greater anxiety. This study assessed (1) whether perceived vulnerability to disease was associated with increased anxiety related to COVID-19 and (2) whether this association was moderated or mediated by insomnia symptoms. Methods: 1199 primarily female (n = 845), white (n = 982) participants (mage = 30.52) completed an online survey including the Sleep Disorder Symptom Checklist- 25 (SDS-CL-25), Perceived Vulnerability to Disease (PVD) scale, and a rating of COVID-19 anxiety (scale = 0–100; m = 55.81, sd = 25.39). Insomnia symptoms were calculated using the sum of SDS-CL-25 items 3–6 (m = 7.55, sd = 3.58). The PVD subscales germ aversion (GA; m = 4.18, sd = 1.22) and perceived vulnerability to infection (PVI; m = 3.69, sd = 1.39) were also computed. Results: Regressions were used to test if insomnia mediated the impact of GA and PVI on COVID-19 anxiety. The relations between COVID-19 anxiety and insomnia (b = 1.30, t(1197) = 6.47), GA (b =3.60, t(1197) = 6.09), and PVI (b =3.73, t(1197) = 7.20) were significant (p's < .001). Mediation analyses using the mediation package in R (bootstrap estimation = 1000 samples) showed direct effects of GA (b = 3.26, 95% CI = 2.04 – 4.42, p < .001) and PVI (b = 3.16, 95% CI = 2.00 – 4.22, p < .001) and mediation effects of insomnia (b =.44, 95% CI = .19 - .73, p < .001; b =.58, 95% CI = .33 - .86, p < .001, respectively). According to the moderation analyses, the association between PVD and COVID-19 anxiety did not significantly vary at different levels of insomnia. Conclusion: Results suggest insomnia symptoms partially mediate the relationship between perceived vulnerability to disease and COVID-19 anxiety. These associations are likely bidirectional, and therefore, more work in this area is needed, especially with regard to how improved sleep may attenuate risk factors for anxiety. Support (if any): K23HL141581 (PI: Vargas)